El acrecentamiento de delitos cibernéticos y la violación a la intimidad por cookies en Ecuador. - Peñafiel Oleas, Julio Humberto (2025)
The objective of this study is to analyze the growth of cybercrime that is being experienced worldwide with Ecuador being no exception. This phenomenon, which is driven by the increasing dependence on technology and sophistication of tools used by cybercriminals has resulted in significant economic losses and affected the reputation of individuals and organizations through an exhaustive review of laws focused on avoiding this type of crimes as well as interviews with users throughout digital platforms to obtain perceptions about this phenomenon. The results revealed that, on one side, the cookies are important for web pages, on the other side, they are the key for the cybercriminals can access our personal information and and cause considerable harm to our economy, private life, and social aspects in which we are involved; however, there are still significant challenges in the legislation to regulate these cookies within our national territory, especially in relation to the contemporary world and the citizenship. In conclusion, this study highlights the importance of laws to safeguard the citizens’ data which are shared in the cookies of the web; protecting their privacy in the digital environment as a user; however, there is still work to be done and guarantee a greater effectiveness in laws regarding how cookies work within the country and web pages accessed. It is fundamental to address these gaps with cookies and it is recommended to strengthen education on these topics